2D Conductive MOFs Intercalated in MXene Interlayer for Fast and Trace Detection of Triethylamine at Room Temperature - Hao Zhang; Wei Cao; Jingfeng Wang; Lei Guo; Pu‐Hong Wang; Zhi‐Jun Ding; Lingmin Yu (Advanced Science)
Abstract Metal–organic frameworks (MOFs) are newly developed materials for gas sensing applications currently. However, the prolonged response time limits their future applications because of their poor electrical conductivity. In this context, alternating stacked MXene@Cu‐HHTP heterostructures characterized by a sandwich‐type architecture comprised of Cu‐HHTP (copper‐catecholate frameworks), 2D conductive MOFs, and layered MXene achieve high‐performance triethylamine (TEA) sensing. The unique interlayer pore architecture within the MXene@Cu‐HHTP composites facilitates efficient mass transfer of gas molecules while retaining the large surface area and porosity characteristics of the MOFs, leading to rapid TEA response. MXene@Cu‐HHTP composites respond to 50 ppm TEA in only 4 s and low detection limit (1 ppm). Demonstrated higher sensitivity compared to the original Cu‐HHTP sensor (≈21 times at 200 ppm TEA). At room temperature and atmospheric conditions, the value of moisture resistance of MXene@Cu‐HHTP composites can reach 80% through continuous real‐time dynamic testing.